Economic optimization of a residential micro-CHP system considering different operation strategies. (25th May 2016) - Caliano, Martina; Bianco, Nicola; Graditi, Giorgio; Mongibello, Luigi
Highlights: The optimal operation of a micro-CHP system is analyzed. The micro-CHP system provides heat and electricity to a multi-apartment housing situated in Italy. Heat dumping effects on the micro-CHP system operation are analyzed. TRNSYS simulations have demonstrated the effectiveness of heat dumping. Abstract: In this work the economic optimization of a micro-CHP system producing electricity and heat during the cold season, for a multi-apartment housing situated in Italy, is addressed. The system is composed of a prime mover, fed by natural gas, a thermal energy storage system and an auxiliary boiler. Two heat-led operational strategies have been implemented in order to evaluate the operation scheduling that maximizes the revenues for the energy cogeneration with respect to the separate generation. The first strategy limits the prime mover production to the user heat request and the heat required to fill the thermal energy storage, while the second novel one permits to have thermal energy produced in excess by the prime mover, or rather it allows to have heat dumping. The analysis of the micro-CHP system has been realized using two different solvers, namely, a home-made numerical code written in Matlab environment, that has been used in order to perform the economic optimization of the micro-CHP system operation, and the commercial software TRNSYS 17, used to carry out the dynamic simulation of the micro-CHP system. The main result of the present study is represented by the demonstration of the practical feasibility of the operation resulting from the economic optimization of the micro-CHP system, for both the analyzed operation strategies.